Effectiveness of Meaningful Instructional Design in Improving Students' Mathematical Skills - Fredi Ganda Putra; Rizki Wahyu Yunian Putra; Sandra Ricardo; Santi Widyawati; Davron Aslonqulovich Juraev (Journal of Philology and Educational Sciences)
This study aims to examine the impact of the Meaningful Instructional Design (MID) model on students' mathematical analytical skills, addressing a gap in previous research, which has yet to explore this critical cognitive domain. A quantitative approach was used with a quasi-experimental method involving two groups: an experimental group that applied the MID model and a control group that used conventional teaching methods. Measurements were conducted through a posttest to assess students' analytical skills in both groups. The results show a significant difference in mathematical analytical abilities between students who used the MID model and those who followed conventional methods, with the MID group achieving higher average scores. In conclusion, the MID learning model proved to be more effective in enhancing students' mathematical analytical skills compared to conventional teaching methods. These findings suggest that meaningful and contextual learning has great potential for optimizing students' analytical skills in mathematics.